HDI XMAS July 15, 2019. Geraldine Legge photos. - Barrett, Terra
A black and white photo of the SUF Band holding their instruments. Theophileus Chislett, Jonas Sooley, Roy Legge, George Sooley, George Hedley Harnum, and Francis Sooley.